Web-Based Job Training Report Guidance System at SMKN 2 Kraksaan - Khairi, Matlubul (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
Implementation of Field Work Practices (PKL) is an effort that can be made by SMK to continue to produce graduates who can compete in the business world and the industrial world (DU / DI). The government policy regarding learning at / from home during the Coronavirus Disease 2019 (COVID-19) pandemic has an impact on the reporting process at SMKN 2 Kraksaan. This study aims to build a report guidance system using server side-based web technology. This system was built using a waterfall model and PHP (PHP Hypertext Prepocessor) programming. System design tools used are Flowmap Diagrams, Data Flow Diagrams, and Entity Relationship Diagrams. The black box test results show that the output of the system is in line with expectations. User response to the system using a questionnaire resulted in a feasibility percentage of 83.6% with a very feasible category interpretation. It can be concluded from the test results that the Field Work Practices report guidance system is in accordance with user needs and is very suitable for use.